Penanganan post traumatic stress disorder melalui trauma healing bagi pramuka peduli - Jufri, Muhammad; Bakhtiar, Muhammad Ilham; Aras, Muhammad (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2016)
The purpose of activity is (1) to improve the knowledge of Scouting Care in Post Traumatic Stress Disorder overcome through Trauma Healing, (2) To improve the technical skills of Trauma Healing. The method used in this activity are: the percentage method, lecture and question and answer, discussion methods, methods of practice. The results of these activities are (1) there is an increased knowledge of participants in following the activities, especially in implementing and applying the theory and practice of PTSD to handling, from the data worksheet that was analyzed contained 94.5% of the questions as an evaluation materials may be answered by the participants. This indicates that the participant understands and is able to apply the techniques of PTSD very well in dealing with post-disaster stress. (2) Participants skillfully PTSD through psychotherapy techniques such as: deepbreating, relaxation techniques, storytelling/story telling, play therapy/role playing and games-games. From a practice several times, through observation through direct observation, illustrating that the participants could perform well in groups or individually.